(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
This study tackles a critical issue in ship design: propeller-induced vibrations in the hull. We propose a novel mechano-mathematical model that goes beyond previous approaches to elucidate the excitation of these oscillations. Our model incorporates the crucial dynamic connection between the propeller's rotational motion and its oscillations. This refinement allows for a more precise understanding of how propellers, even when mechanically balanced, can excite vibrations through hydrodynamic imbalances. The traditional approach relies on simpler models, often leading to qualitative analysis. This work advances the field by introducing a more robust mechano-mathematical framework. This framework considers the complex interaction between the main engine, shaft line, and propeller, including factors like engine torque variations, propeller moment, and elastic properties of the system. The model is not just theoretical. We present experimental results that validate the spectral components predicted by our model. This successful validation demonstrates the model's accuracy in capturing the real-world dynamics of propeller-induced vibrations. The practical implications of this work are significant. By pinpointing the excitation mechanisms with greater precision, this research can pave the way for the development of improved propeller designs that minimize vibrations. Reduced vibrations translate to enhanced crew comfort, lower maintenance requirements, and potentially even improved fuel efficiency. Additionally, the model can be a valuable tool for optimizing ship powerplant design to ensure smooth operation and extended lifespan.